Sitagliptin for the prevention and treatment of perioperative hyperglycaemia in patients with type 2 diabetes undergoing cardiac surgery: A randomized controlled trial. Issue 2 (2nd December 2020) - Cardona, Saumeth; Tsegka, Katerina; Pasquel, Francisco J.; Jacobs, Sol; Halkos, Michael; Keeling, W. Brent; Davis, Georgia M.; Fayfman, Maya; Albury, Bonnie; Urrutia, Maria A.; Galindo, Rodolfo J.; Migdal, Alexandra L.; et al.
Abstract: Aim: To assess whether treatment with sitagliptin, starting before surgery and continued during the hospital stay, can prevent and reduce the severity of perioperative hyperglycaemia in patients with type 2 diabetes undergoing coronary artery bypass graft (CABG) surgery. Materials and Methods: We conducted a double‐blinded, placebo‐controlled trial in adults with type 2 diabetes randomly assigned to receive sitagliptin or matching placebo starting 1 day prior to surgery and continued during the hospital stay. The primary outcome was difference in the proportion of patients with postoperative hyperglycaemia (blood glucose [BG] > 10 mmol/L [>180 mg/dL]) in the intensive care unit (ICU). Secondary endpoints included differences in mean daily BG in the ICU and after transition to regular wards, hypoglycaemia, hospital complications, length of stay and need of insulin therapy. Results: We included 182 participants randomized to receive sitagliptin or placebo (91 per group, age 64 ± 9 years, HbA1c 7.6% ± 1.5% and diabetes duration 10 ± 9 years). There were no differences in the number of patients with postoperative BG greater than 10 mmol/L, mean daily BG in the ICU or after transition to regular wards, hypoglycaemia, hospital complications or length of stay. There were no differences in insulin requirements in the ICU; however, sitagliptin therapy was associated with lower mean daily insulin requirements (21.1 ± 18.4 vs. 32.5 ± 26.3 units, P = .007) after transition to a regular ward compared with placebo. Conclusion: The administration of sitagliptin prior to surgery and during the hospital stay did not prevent perioperative hyperglycaemia or complications after CABG. Sitagliptin therapy was associated with lower mean daily insulin requirements after transition to regular wards.